2005
DOI: 10.5902/198050981870
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de mudas de <i>Jacaranda puberula</i> Cham. em viveiro submetidas a diferentes níveis de luminosidade.

Abstract: RESUMOJacaranda puberula, conhecida como caroba, é uma espécie que apresenta potencial de uso para recomposição de áreas degradadas, por possuir rápido crescimento, agressividade e adaptar-se bem a solos arenosos e argilosos, ocorrendo em capoeiras e capoeirões. Com o intuito de se obter informações sobre espécies potenciais para uso em restauração de ambiente ripário foi estudado, no viveiro da prefeitura do município de Colombo, o desenvolvimento de mudas de Jacaranda puberula submetidas a 0, 30, 50 e 70% de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 7 publications
5
17
0
14
Order By: Relevance
“…In this case, it would not be a viable option because a good root volume is essential for citric seedling production. A similar result was obtained by Almeida et al (2005), in which the seedlings of Jacaranda puberula showed higher concentration of biomass in the dried root at 30% and 50% shading, respectively. Tambelini and Perez (2007) found that the species Bauhinia holophylla (Bong.)…”
supporting
confidence: 73%
“…In this case, it would not be a viable option because a good root volume is essential for citric seedling production. A similar result was obtained by Almeida et al (2005), in which the seedlings of Jacaranda puberula showed higher concentration of biomass in the dried root at 30% and 50% shading, respectively. Tambelini and Perez (2007) found that the species Bauhinia holophylla (Bong.)…”
supporting
confidence: 73%
“…According to Almeida et al, (2005) this is possible due to the greater area of water and nutrients absorption and the greater capacity of sustainability of seedlings. As most of the variables are strongly correlated and bearing in mind that the dry mass represents the net photosynthesis, seedlings of C. trichotoma produced in container of 110 cm³ demonstrated better quality, however it becomes relevant care with the maintenance in post planting, especially, with the control of invasive herbaceous species capable of competing with the seedlings for water and nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed in seedlings of Jacaranda puberula Cham. produced in December, which presented a mean survival rate of 84.3% after 120 days of pricking out (ALMEIDA et al, 2005).…”
Section: Resultsmentioning
confidence: 99%